2008
DOI: 10.1038/ejhg.2008.121
|View full text |Cite
|
Sign up to set email alerts
|

What process attributes of clinical genetics services could maximise patient benefits?

Abstract: There is limited evidence about what process attributes of clinical genetics services may be highly valued by patients and service providers. The aim in this qualitative grounded theory study was to explore what process attributes may be highly valued by those stakeholders. Seven focus groups (n ¼ 33) and nineteen one-to-one interviews were conducted (total sample size ¼ 52). Five process attributes were identified as highly valued by patients and health professionals: (1) local and accessible services (2) ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
2
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 29 publications
0
36
2
4
Order By: Relevance
“…A growing body of evidence supports the significant role played by physicians and other providers in improving adherence in this population [13,16,33,34,43]. It is therefore important that all providers become informed about current screening and treatment protocols [16,35,48]. …”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence supports the significant role played by physicians and other providers in improving adherence in this population [13,16,33,34,43]. It is therefore important that all providers become informed about current screening and treatment protocols [16,35,48]. …”
Section: Discussionmentioning
confidence: 99%
“…For decades there has been a need for more appropriate tools to measure the benefits of genetic testing and genetic counselling services, [8][9][10] but there is still a need to further operationalize the concept of benefit in relation to genetic testing. The authors of the paper have not defined genetic testing, but it is to be assumed that they refer not only to the laboratory component, but also the clinical counselling support involved.…”
mentioning
confidence: 99%
“…However, as many studies have consistently found, adequate follow-up is associated with improved psychosocial outcomes for patients and their families who value follow-up appointments for a range of reasons beyond clinical utility. 23,24,28 Providing hope Doctors demonstrated a strong epistemic stance towards future improvements in technology and knowledge suggesting strong commitment to these statements. This strong epistemic stance may suggest that doctors are confident the improvements will eventuate.…”
Section: Review Appointmentsmentioning
confidence: 99%